PSVII-31 Management and production practices adopted by goat farmers in Punjab province of Pakistan. - Moaeen-ud-Din, M (J Anim Sci, 2018)
A survey was carried out to gather information for documenting the goat farming system in the province Punjab (included districts of Fateh Jhang, Bakhar, Liayyah, D.G. Khan, Rajanpur, Faislabad and Jhang). The objective of survey was to highlight the constraints of farmers. Survey was carried out for seven goat breed of Province Punjab viz. D.D.P., Nachi, Barbari, Teddi, Beetal, Pahari and Potohari. Seventy farmers were visited and 51.61% did vaccine the animals on regular basis. Farmers used vaccinations against HS (7.41%), anthrax (59.26%), FMD (92.59 %), Enterotoxaemia (14.81%), PPR & CCPP (74.07%). For parasitic control 29.03% farmers dewormed their herds on regular basis. For ectoparasites 33.33% used medicine regularly while for endoparasites 50% farmers did deworming regularly. About 19.35% farmers believed in traditional treatment while 70.97% farmers got treatment from veterinary doctors on regular basis. Disease outbreak in these herds was mainly FMD (70.97%), CCPP (93.55%) and Enterotoxaemia (74.19%). As far as production system is concerned, in the irrigated areas it was backyard system (22.58%), Agro-pastoralist (16.13%), and crop livestock (48.39%), while in rain-fed areas rangeland base system (48.39%) and agro forestry (6.45%) prevailed. Most of the farmers confined animals at night (90.32%) whereas 64.52 % farmers had sheds for their herds whereas. Other then crop residues and range feed resources, 41.94% farmers used concentrates and 25.81% farmers used mineral mixture. Cross breeding was practiced by 54.84% of the farmers. Breeding season was extended from March to June however; some animals were also bred from August to December. Most of the farmers maneuvered the mating strategies whereas season selection was also practiced for breeding (45.16%) due to weather and doe health maintenance. Most of the farmers marketed live animals to local market (Mandi) through middleman (61.29%). This is useful information for devising strategies for goat improvement.